Analisa Politik Hukum Tata Kelola Mineral Dan Batu Bara Terhadap Kerentanan Konservasi Lingkungan - Manahan Budiarto Pandjaitan; Rachmad Safa'at; Panji Suwarno (AGUSPATI Research Institute, 2023)
This research aims to analyze the impact of political and legal aspects in the governance of mineral and coal resources on the vulnerability of environmental conservation. Mineral and coal mining is a crucial sector in the global economy, but it also has serious impacts on the environment. Political and legal factors have a significant role in regulating these industrial practices. This research uses an interdisciplinary approach to analyze environmental vulnerabilities resulting from the governance of mineral and coal resources, with a focus on existing regulatory frameworks and political policies. We conducted a comprehensive review of the laws governing this sector and analyzed the extent to which these regulations can mitigate negative impacts on the environment. The research results show that the vulnerability of environmental conservation in the governance of mineral and coal resources is strongly influenced by political policies and the legal framework in place There is. Policies that are less stringent or weakly implemented can increase the risk of environmental damage. Therefore, this research provides recommendations for improving legal and policy frameworks that are more sustainable and environmentally friendly in the governance of the mineral and coal sectors. This research is expected to provide important insights to policy makers, industry stakeholders and the general public about the importance of integrating environmental aspects in mineral and coal resource management policies, as well as encouraging positive changes in environmental conservation efforts in this sector.